Micro-Mobility Infrastructure for Redefining Urban Mobility (European Journal of Engineering Science and Technology, 2020)
As the cities grow and their population increase, there is an intensifying claim for primary components such as housing, transportation, utility services, water supply, etc. Integrated and inclusive urban transportation infrastructure addresses dual purposes - mobility and access to various urban facilities. Urban mobility is no longer only about movement of people in urban areas. In the current milieu of increased preferences for personal motorised transport over public transport, there is a need to redefine and restructure urban mobility through planned integrated Rapid Mass Transit (RMT) hubs while harnessing the ICT (Information and Communication Technology) enabled services to unambiguously offer diverse mobility choices for providing inclusive and accessible (spatially and socio-economically) urban spaces. Against this background, this research paper through a case example attempts to understand and analyse the major trends that are deciding the modes of urban mobility with a focus on micro-mobility infrastructure which is a vital component in addressing the first and last mile connectivity for the efficient usage of rapid mass transit system. Further, key strategies are proposed to augment the planning and implementation of micro-mobility options to improve and redefine the urban mobility.